ASPEK-ASPEK PSIKOLOGI UPACARA RITUAL LALUHAN PADA MASYARAKAT DAYAK NGAJU - Fiona Anggreni; Jatie K. Pudjibudojo (PSIKOVIDYA, 2021)
Abstract. This literature study aims to explain the tradition of the Laluhan ceremony from a psychological perspective especially in the aspects of commitment and conformity of the Dayak Ngaju tribe. The Laluhan ritual is a process of delivering goods / assistance to the place where Tiwah's death party is held. Based on the beliefs of the Dayak Ngaju tribe, it will have a good impact when equipping the spirits of ancestors and families who have passed away to lewu tatau (heaven). In the process of implementing Bakas Tiwah as the customary leader in charge of conveying the types and quantities of Laluhan items to families and communities. Through Laluhan, social influence is carried out on their offspring and encourages the community to become conformists in the group to do the same thing and try to fulfill the commitment to achieve the group's goals. The Benefits of Research contribute knowledge to the public about the culture of death in Central Kalimantan. Keywords: Dayak ngaju, Laluhan, ritual ceremony